Limnological Parameters and Population Structure of Artemia persimilis Piccinelli and Prosdocimi, 1968 (Crustacea, Anostraca) in La Amarga, a Hypersaline Lake of La Pampa (Argentina) - Echaniz, Santiago Andrés (2015)
In the semiarid central region of Argentina, there are many hypersaline lakes that are scarcely studied ecologically. In La Pampa province, La Amarga stands out, which is a lake with particular characteristics that belongs to a virtually inactive fluvial system by anthropogenic action. Since Artemia persimilis Piccinelli and Prosdocimi, 1968, a native species on which information is scarce, has been registered in La Amarga, the objectives of this study were to determine the main limnological parameters and know the density, biomass and population structure of A. persimilis and its relationship with environmental parameters. Seasonal samplings (January, April, August and October) were carried out during 2007. In situ temperature, dissolved oxygen concentration, pH and transparency were determined. Water samples were taken for the determination of salinity, nutrients, suspended solids and chlorophyll-a and qualitative and quantitative zooplankton samples. The mean salinity was 115 g.L-1 ±19.02 and Cl- and Na+ predominated. Mean transparency was 1.54 ±0.15 m, and despite high concentrations of nutrients (TP: 4.38 ±1.61 mg.L-1 and TKN: 25.32 (±12.29) mg.L-1), the phytoplankton chlorophyll-a concentration was reduced (1.65 ±1.16 mg.m-3). The mean density and biomass of A. persimilis were reduced (1.56 ±2.17 ind.L-1 and 122.43 ±99.3 µg.L-1). The density was minimal in winter (0.04 ind.L-1), but was higher when more biomass was found (240.95 µg.L-1), since larger stadiums (post-larvae and adults) prevailed. No correlations between total density and biomass or those of the different stages and environmental parameters were found. Although A. persimilis has adaptations that allow it to thrive with higher salinities than those of La Amarga, its low density and biomass could be due to scarce availability of food, given the low concentrations of chlorophyll-a and suspended organic solids that were recorded.